EXPLORING THE EFFECTIVENESS OF TECHNOLOGY IN ENHANCING SPEAKING SKILLS AMONG EFL LEARNERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The integration of digital technologies in language education has significantly transformed the teaching and learning of English as a Foreign Language (EFL), particularly in the development of speaking skills. This study critically examines the effectiveness of technology-enhanced instruction in improving learners’ fluency, pronunciation, and communicative confidence. Employing a qualitative synthesis of recent scholarly literature and classroom-based evidence, the study explores the pedagogical role of mobile applications, artificial intelligence (AI)-driven speech recognition systems, and online communication platforms. Findings suggest that technology fosters a learner-centered environment by reducing speaking anxiety, increasing exposure to authentic language input, and enabling autonomous practice. However, the study also identifies critical limitations, including overdependence on digital tools, reduced face-to-face interaction, and disparities in technological accessibility. The study concludes that technology is most effective when integrated within a structured pedagogical framework supported by teacher mediation.